La zone canadienne des 200 milles dans l’Atlantique, un exemple de la nouvelle géographie politique des océans - Sanguin, André-Louis (Études internationales, 1980)
Following upon the Third Conference on the Law of the Sea begun in 1973, the principal maritime States of the world assumed exclusive national jurisdiction over a 12- mile zone extending from their coastlines and a 188-mile economic zone beyond territorial waters. Together they constitute the more familiarly referred to « 200-mile zone ». This new practice radically changed the political geography of the oceans, lessened the area within which the freedom of the seas exists, diminished by more than a third the surface area of the high seas and dealt a heavy blow to the fishing xpeditions of foreign trawlers. Canada is one of the principal users and one of the most vigourous defenders of the 200-mile principle for geographical reasons as much as for economic or political ones. The excessive exploitation of the seabed has been felt to be a threat for a portion of the population of the Eastern part of Canada. A firm policy criticized for being somewhat unilateral has enabled Canada to eliminate foreign fleets from its 200-mile zone. Over a period of 30 years the International Commission for North-West Atlantic Fisheries (ICNAF) attempted to introduce a positive international cooperation in order to eliminate the anarchic excessive exploitation. It was replaced in 1979 by the North-West Atlantic Fisheries Organization. A major dispute exists between France and Canada with respect to the delimitation of the economic zone of Saint-Pierre and Miquelon, French land since 1604. More generally, the question is posed as to how long the 200-mile principle will prevail in this new political geography of the oceans.